Pengembangan UMKM Di Kawasan Wisata Religi Sunan Sendang Berbasis Nilai-Nilai Syariah - Shofiyah; Aziq Nur Aiman (Al-Musthofa: Journal of Sharia Economics, 2025)
This study aims to analyze the potential and challenges of developing Micro, Small, and Medium Enterprises (MSMEs) around the Sunan Sendang Religious Tourism area in Sendangduwur Village, Paciran District, Lamongan Regency, based on sharia values. The research approach used is descriptive qualitative with a case study method, through interviews, observations, and documentation of MSME actors, tourism managers, and the village government. The results of the study indicate that the potential of religious tourism contributes significantly to increasing community income through trade, transportation services, and craft products. However, the development of MSMEs still faces major obstacles such as limited capital, low innovation, and limited access to training and business digitalization. Comparative analysis with other religious tourism locations such as Sunan Drajat and Syaikhona Kholil shows that the success of MSME development is greatly influenced by institutional synergy and the application of Sharia principles. This study concludes that strategies for strengthening MSMEs need to be directed at collaboration between stakeholders, strengthening Islamic business ethics, and digital innovation based on values ​​of justice and the welfare of the community.